2011
DOI: 10.1111/j.1399-3062.2011.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cerebral manifestation of Epstein–Barr virus‐associated post‐transplant lymphoproliferative disorder after allogeneic hematopoietic stem cell transplantation: a case of clinical and diagnostic challenges

Abstract: We present the case of a 49-year-old male patient with Epstein-Barr virus (EBV)-associated post-transplant lymphoproliferative disorder (PTLD) limited to the brain that occurred 6 months after allogeneic hematopoietic stem cell transplantation (HSCT). Clinical symptoms included mental confusion, ataxia, and diplopia. Magnetic resonance imaging (MRI) revealed cerebellar and periventricular lesions consistent with an inflammatory process. Cerebrospinal fluid (CSF) analysis, but not peripheral blood, was positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
(61 reference statements)
1
24
1
Order By: Relevance
“…EBV-DNA loads of blood are acted as the main basis for diagnosis, preemptive therapy and therapeutic evaluation, but our study and others cases reports [12,13] showed that special EBV-associated disease in CNS and pulmonary had the discrepancy in EBV-DNA loads; sometimes repeated testing with real-time PCR in peripheral blood failed to show any evidence of EBV reactivation, and the change of EBV-DNA loads of blood was inconsistent with disease development. But frequent quantitative monitoring of EBV viral load in high-risk patients is still important to prevent occurrence of EBV-PTLD [14].…”
contrasting
confidence: 55%
“…EBV-DNA loads of blood are acted as the main basis for diagnosis, preemptive therapy and therapeutic evaluation, but our study and others cases reports [12,13] showed that special EBV-associated disease in CNS and pulmonary had the discrepancy in EBV-DNA loads; sometimes repeated testing with real-time PCR in peripheral blood failed to show any evidence of EBV reactivation, and the change of EBV-DNA loads of blood was inconsistent with disease development. But frequent quantitative monitoring of EBV viral load in high-risk patients is still important to prevent occurrence of EBV-PTLD [14].…”
contrasting
confidence: 55%
“…In immunocompromised individuals, herpesvirus-associated CNS diseases, such as encephalitis/myelitis and lymphoproliferative diseases, are representative of acute complications [12-14]. Since specific therapy is limited to only several viral agents, accurate diagnosis and early therapy reduces the extent of permanent injury in survivors and positively influences survival rate [15].…”
Section: Introductionmentioning
confidence: 99%
“…Five previous case reports have described a negative EBV PCR of the peripheral blood in the presence of an EBV‐positive PTLD isolated to the CNS [10–14]. See Table 1.…”
Section: Discussionmentioning
confidence: 99%